(untitled) (Innovation & Development in Engineering and Applied Science, 2025)
This project focuses on analyzing the wear of SIE engines with oils of different viscosity in the cities of Quito (2850 m.a.s.l.) and Santo Domingo (655 m.a.s.l.), to identify the wear of the internal elements of the engine through tribological tests. A 2002 Nissan Sentra B15 vehicle was used and extra 87 octane gasoline, several oil filters for each test, lubricants with viscosity grades SAE 10W30 and 20W50. Likewise, measurements were made at different engine speeds, such as 1500 and 2500 rpm. The data obtained in reference to polluting gases allowed us to observe that 10W30 oil generates higher polluting emissions and higher maintenance costs. Finally, the tribological tests and trials show that oils with the same specification and different atmospheric pressure and viscosity grade, generate different wear on the internal components of SIE engines.